SOCIALIZATION OF DISEASES NOT COVERED BY BPJS KESEHATAN AND THE IMPORTANCE OF USING ADDITIONAL COMMERCIAL INSURANCE - Septivani, Nike; Indra, I Made (Yayasan Education and Social Center, 2025)
Many people do not fully understand the types of diseases that BPJS Kesehatan and the benefits of additional health insurance do not cover. Therefore, socialization is needed so people can make the right decisions in their financial and health planning. This Community Service (PkM) was carried out in the Even Semester of the 2024/2025 Academic Year, with its peak activity on June 3, 2025, where STMA Trisakti successfully held a PKM Seminar with the theme